(untitled) (Journal of Oriental Studies, 2017)
The article considers semantic structural peculiarities of political terms and the way of their formation, the questions of their adequate use age in accordance to the demands of the contemporary time in the frame of arab biography, general linguistics and the questions of the influence of global process to term formation , published in the article “Al-Ahram” newspaper.